PATHOMORPHOLOGICAL AND COMPUTERIZED TOMOGRAPHY STUDY OF IBUPROFEN AND COMBINATION WITH 2-PHENYL-3-CARBETHOXY-4-DIMETHYLAMINOMETHYL-5-OKSIBENZOFURAN HYDROCHLORIDE (VINBORON) INFLUENCE ON THE JOINTS OF LOWER EXTREMITIES OF RATS WITH EXPERIMENTAL RHEUMATOID ARTHRITIS - F. V. Hladkykh; V. O. Student; N. H. Stepaniuk; S. V. Vernyhorodskyi (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2017)
The most frequent adverse reactions to nonsteroidal anti-inflammatory drugs are upper and lower gastrointestinal tract disorders, hepatotoxicity, nephrotoxicity, a decrease in the synthesis of proteoglycans of the cartilaginous tissue and allergic reactions. In our previous studies we have found out that Ukrainian vinboron, the antispasmodic with polytrophic pharmacological effects, can improve the safety profile of the popular non-steroidal antiphlogistics ibuprofen and can also potentiate its anti-inflammatory effect. That fact has become the background to a detailed study of the therapeutic action mechanisms of these drugs when they are used together.Aim of the study. To characterize the influence of vinboron (11 mg/kg, i.g.) on the anti-inflammatory activity of ibuprofen (218 mg/kg, i.g.) when combined, in a model of experimental rheumatoid arthritis according to pathomorphological, morphometric and cone-ray computerized tomography of rats' hind limbs.Materials and methods. To reproduce the conditions for the administration of ibuprofen corresponding to its clinical use, we selected a model of experimental rheumatoid arthritis-adjuvant arthritis (AA) in rats. On the 28th  day the animals were excluded from the experiment. It was followed by the amputation of the hind limbs at the level of the hocks (art. coxae) and fixation of the material in 10.0% aqueous solution of neutral formalin. The ankle joints were decalcified. The drugs were prepared according to the standard procedure. Microscopy and photographing of histological preparations were carried out with the light microscope OLIMPUS BX 41 at magnifications of 40, 100, 200 and 400 times. The obtained images were processed and morphometry was carried out with the program "Quick PHOTO MICRO 2.3". The contents of the cellular elements was determined on the basis of the equivalent unit area (1 mm2). Cone-ray computerized tomography was carried out with a digital panoramic cone-ray tomographic scanner "Point 3D Combi 500" (PointNix, South Korea), using a planar sensor with a scanning site of 9 × 12 mm and a radial load of 30-100 μSv. Scanning was carried out with a voltage of 52.0 kV and the electric current of 6.0 mA. For the integral characteristics of the linear dimensions of rats' hind limbs joints we proposed a formula for calculating the joint volume (Patent of Ukraine No. UA 117538). For the integral characteristics of the dimensions of rats' hind limbs linear joints we proposed a formula for calculating the joint volume (Patent of Ukraine No. UA 117538).Results and discussion. The use of ibuprofen in combination with vinboron was accompanied by restoration of the structure and function of the cartilage and bone tissues, evidenced by the appearance of acidic and sulfated glycosaminoglycans. The restoration of the bone tissue was realized by the proliferation of the connective tissue and its transformation into cartilage. The synovial membrane was hyperplastic with proliferating synoviocytes of both macrophage and secretory types. In rare cases, the phenomenon of moderate edema and minor focal lymphohistiocytic infiltration persisted. Thus, the use of ibuprofen and ibuprofen in combination with vinboron in rats with adjuvant arthritis resulted in a reduction or absence of inflammation in both the joint and periarticular tissues. The analysis of the results of cone-ray computerized tomography and digital radiography showed that against the background of simultaneous administration of ibuprofen and vinboron there was a tendency to increase the anti-inflammatory effect of the studied antiphlogistics on the rats' joints affected by adjuvant arthritis. On the 28-th day of the experiment there was the indicatation of decrease of the volume of the hind limb joints by an average of 33.8% compared to the control animals and a near-complete restoration of the width of the joint gaps of the joints examined. It was also determined that vinboron can harmonize the anti-inflammatory effect of ibuprofen when they are used together.Сonclusion. The use of vinboron in combination with ibuprofen leads to a more pronounced pathogenetic anti-inflammatory structural-modifying effect of this antiphlogistics.